Parenteral nutrition and drug interactions: A literature review (Research, Society and Development, 2023)
Parenteral Nutrition (PN) involves the direct administration of nutrients into the bloodstream and is crucial when oral or enteral feeding is unfeasible. However, its combination with medications can lead to detrimental interactions. This study aimed to understand the primary consequences of these interactions through a narrative literature review (2013-2023). From the results, 50% of the studies emphasized the need for rigorous patient monitoring to prevent complications arising from interactions. It was found that 80% of the studies indicate a direct impact on patients' nutrition, resulting in a decrease in the absorption of essential nutrients, considering the individualized prescription of PN. Toxicity caused by drug interactions in PN was highlighted in 90% of the research, underscoring the need for improvements in this aspect. Additionally, 60% of the authors pointed out insecurity in medication administration, emphasizing the importance of training professionals in PN. The effectiveness of pharmacological treatment was reduced in 80% of cases, while 70% highlighted an increased risk of side effects. In conclusion, the study revealed a scarcity of research on the topic, emphasizing the need for more specific investigations into the consequences of drug interactions in PN.